Internal Use of Ajan Vruksha/ Khandu Chakka (Ehretia Laevis Roxb). Plant Leaves Powder in Shoulder Pain Management. – Case Report - Rushikesh Thakre; Abhyuday Meghe; Ketaki Thakre; Pradip Tekade (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction— Shoulder pain and stiffness are common features among working women. It is affectingtheir day to day life style.The main symptoms of the patient and the important clinical findings:- Patient was suffering fromsevere pain in right shoulder with restricted movement of right shoulder from 8 days. Patient was assessedby ( SPADI) Shoulder Pain & Disability Index.The main diagnoses, therapeutics interventions, and outcomes:- Ehretia Laevis Roxb. leaves powdercapsules was made up of 250 mg. Patient was advised to take two capsules in morning and two capsules atnight after food. Daily 1 gm powder was administered internally for 7 daysOn the day zero pain score was 80%, on third day of treatment pain score was 54% and on seventh day painscore was 0. On the day zero disability score was 95%, on third day disability score was 55% and on seventhday score was 0.Conclusion—. Patient cured from pain and shoulder disability by internal use of Ehretia Laevis Roxb.leaves powder within seven days